2021
DOI: 10.1186/s12967-021-03015-w
|View full text |Cite
|
Sign up to set email alerts
|

Multi-parametric MRI phenotype with trustworthy machine learning for differentiating CNS demyelinating diseases

Abstract: Background Misdiagnosis of multiple sclerosis (MS) and neuromyelitis optica (NMO) may delay the treatment, resulting in poor prognosis. However, the precise identification of these two diseases is still challenging in clinical practice. We aimed to evaluate the value of quantitative radiomic features extracted from the brain white matter lesions for differential diagnosis of MS and NMO. Methods We recruited 116 CNS demyelinating patients including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Based on the assumption that medical imaging contains exploitable information reflecting underlying pathophysiology, the radiomics approach utilizes the extraction and subsequent analysis of various standardized radiomic features from radiological images. In recent years, radiomics has shown promising potential beyond its original application in oncology imaging [ 20 , 21 , 33 , 34 ]. However, application to AE has been less extensively studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the assumption that medical imaging contains exploitable information reflecting underlying pathophysiology, the radiomics approach utilizes the extraction and subsequent analysis of various standardized radiomic features from radiological images. In recent years, radiomics has shown promising potential beyond its original application in oncology imaging [ 20 , 21 , 33 , 34 ]. However, application to AE has been less extensively studied.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies have shown radiomics’ potential in differentiating demyelinating diseases of the central nervous system [ 20 ], identifying Parkinson’s disease subtypes [ 21 ] and discriminating grade II glioma from brain inflammation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This sensitivity and specificity surpass VEP, where the sensitivity for predicting MS diagnosis in adults ranges between 20% and 50% in children with clinically isolated syndromes, and 25% and 50% in children with clinically definite MS. 20 , 21 Importantly, the sensitivity and specificity of OCT in diagnosing MS comes close to that of the current diagnostic gold standard, MRI. Studies looking at binary classification between MS and controls 22 , 23 or MS and NMOSD 24 using artificial intelligence have reported high sensitivity at 96% and 87%, respectively. Our results suggest that auto-segmented OCT features may be as useful and readily clinically applicable in diagnosing MS in children without any a priori criteria, although MRI may have greater sensitivity and specificity when screening for other pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al [37] collected magnetic resonance images of 116 patients with demyelinating diseases of the central nervous system (including 38 cases of NMO and 78 cases of MS). Based on radiological and clinical features, a The accuracy, sensitivity, specificity, and F1 scores of network A were 0:863 ± 0:055, 0:750 ± 0:136, 0:896 ± 0:042, and 0:712 ± 0:121, respectively; the accuracy, sensitivity, specificity, and F1 scores of network B were 0:855 ± 0:018, 0:821 ± 0:071, 0:865 ± 0:021, and 0:719 ± 0:040, and the AUC values of the two networks were 0.922.…”
Section: Application Of Ai Image Analysis In Optic Neuromyelitismentioning
confidence: 99%